Дымовая завеса: романы / Дик Френсис ; пер. с англ. : - Френсис Дик (Классика детектива, 2004)
Экземпляры: . (2007.09.14) / Инвентарный номер: 43450 / Цена: / Сис.шифр: И(Англ) / Авт.знак: Ф87 / ББК: И(Англ)